Trends, etiologies, and predictors of 90‐day readmission after percutaneous ventricular assist device implantation: A national population‐based cohort study. Issue 5 (10th May 2018) - Virk, Hafeez Ul Hassan; Tripathi, Byomesh; Gupta, Shuchita; Agrawal, Akanksha; Dayanand, Sandeep; Inayat, Faisal; Krittanawong, Chayakrit; Ghani, Ali Raza; Zabad, Mohammad Nour; Krishnamoorthy, Parasuram Melarcode; Amanullah, Aman; Pressman, Gregg; et al.
Abstract : Percutaneous ventricular assist devices (pVADs) are indicated to provide hemodynamic support in high‐risk percutaneous interventions and cardiogenic shock. However, there is a paucity of published data regarding the etiologies and predictors of 90‐day readmissions following pVAD use. We studied the data from the US Nationwide Readmissions Database (NRD) for the years 2013 and 2014. Patients with a primary discharge diagnosis of pVAD use were collected by searching the database for International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) procedural code 37.68 (Impella and TandemHeart devices). Amongst this group, we examined 90‐day readmission rates. Comorbidities as identified by "CM_" variables provided by the NRD were also extracted. The Charlson Comorbidity Index was calculated using appropriate ICD‐9‐CM codes, as a secondary diagnosis. A 2‐level hierarchical logistic regression model was then used to identify predictors of 90‐day readmission following pVAD use. Records from 7074 patients requiring pVAD support during hospitalization showed that 1562 (22%) patients were readmitted within 90 days. Acute decompensated heart failure (22.6%) and acute coronary syndromes (11.2%) were the most common etiologies and heart failure (odds ratio [OR]: 1.39, 95% confidence interval [CI]: 1.17–1.67), chronic obstructive pulmonary disease (OR: 1.26, 95% CI: 1.07–1.49), peripheral vascular disease (OR: 1.305, 95% CI: 1.09–1.56), and discharge into short‐ or long‐term facility (OR: 1.28, 95% CI: 1.08–1.51) were independently associated with an increased risk of 90‐day readmission following pVAD use. This study identifies important etiologies and predictors of short‐term readmission in this high‐risk patient group that can be used for risk stratification, optimizing discharge, and healthcare transition decisions.